2018
DOI: 10.1021/jacs.8b08895
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a Bacterial Multidrug Resistance System Revealed by the Structure and Function of AlbA

Abstract: To combat the rise of antimicrobial resistance, the discovery of new antibiotics is paramount. Albicidin and cystobactamid are related natural product antibiotics with potent activity against Gram-positive and, crucially, Gram-negative pathogens. AlbA has been reported to neutralize albicidin by binding it with nanomolar affinity. To understand this potential resistance mechanism, we determined structures of AlbA and its complex with albicidin. The structures revealed AlbA to be comprised of two domains, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Next, we investigated variations in building block F. As we had found out in our previous work, [21] replacing building block F with unsubstituted pABA (compound 14), resulted in an antibacterial activity that was comparable to compound 2.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Next, we investigated variations in building block F. As we had found out in our previous work, [21] replacing building block F with unsubstituted pABA (compound 14), resulted in an antibacterial activity that was comparable to compound 2.…”
Section: Methodsmentioning
confidence: 95%
“…Previously, various resistance factors against albicidin have been characterized. The two main resistant factors are the albicidin binding protein AlbA 20,21 and the serine protease AlbD. 22 To maximize the bioactivity of albicidin in the quest for a potent novel antimicrobial drug, structure-activity relationship (SAR) studies are key.…”
Section: Introductionmentioning
confidence: 99%
“…The TipAS protein is the predominant form that is capable of recognizing thiopeptide compounds via covalent binding by an active cysteine (13,20), which then induces structural reordering to form a large hydrophobic cleft for permanent sequestration and neutralization of the antibiotics (14,18). However, upon thiopeptide binding into the C-terminal TipAS domain, the Nterminus of TipAL (TipAN) is activated to bind promotors via the HTH domain and promote transcriptional activation of multiple genes, including tipA for antibiotic resistance (14,21).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to S. lividans, TipA-class proteins have also been reported to have crucial regulatory functions in other species such as multidrug transporter activation protein (Mta) from Bacillus subtilis (22), stationary-phase regulation of KatG protein (SkgA) from Caulobacter crescentus (23) and Albicidin resistance protein (AlbA) containing two tandem TipAS domains from Klebsiella oxytoca (21,24). Structural analyses using apo and mta promoter-bound structures of the Mta Nterminus (MtaN) revealed that MtaN possesses a canonical MerR-type HTH motif that binds promoter DNA to activate transcription using a distortion mechanism identical to BmrR, which belongs to another MerR-type MDR gene regulator family with a GyrI-like effector domain (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infections pose an unprecedented global challenge to public health, especially with the emergence of antibiotic-resistant pathogens that have developed through the overuse or misuse of antibiotics (Simpson et al., 2009, Han et al., 2011, Chambers and DeLeo, 2009; Rodriguez et al., 2014, Wellington et al., 2013). The continuing emergence and global spread of antibiotic-resistant bacterial strains have generated great interest, from bench researchers in academic laboratories to clinical trials to explore new antibacterial agents that act differently from traditional antibiotics to combat harmful pathogen-associated diseases (Li et al., 2018a, Bunders et al., 2011, Huang et al., 2015a, Sikandar et al., 2018). Compared with traditional antibiotics, antibacterial nanomaterials are not prone to generate bacterial resistance because they not only act through multiple antibacterial mechanisms simultaneously but also have good membrane permeability owing to their small sizes (Li et al., 2018b, Hemeg, 2017, Rigo et al., 2018).…”
Section: Introductionmentioning
confidence: 99%